International students in websites of public and private Universities in Malaysia: a discourse analysis through academic capitalism framing - Daron Benjamin Loo (Universiti Sains Islam Malaysia, 2022)
University websites provide information that may influence international students’ choice of an institution. In the context of Malaysia, studies on university websites remain minimal and highly contextual. To address this gap, this study will conduct a discourse analysis on websites of both public and private universities in Malaysia. A total of 40 websites were selected to form a corpus. The analysis involved the identification of significant collocates for the key words “international” and “student(s)”. These collocates were then discussed through academic capitalism framing. The findings indicated that university websites offered information that was either procedural, or that which explained how an institution was international. This analysis painted international students as customers requiring assistance from a university. Findings also showed that being an international student in Malaysia would bring about social mobility through interactions with other international students.